The Identification Of Library Management Procedure In The School With C Accreditation Status - Lathifah, Zahra Khusnul; Maryani, Novi; Vebriyanti , Mega Milenia (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to identify the library management procedure in schools, using qualitative research and a case study approach. The data analysis technique used is based on the opinion of Miles and Huberman, which consists of three streams of activities that occur simultaneously namely, data reduction, data presentation, and conclusion drawing/verification. The results showed that there was no implementation of a good library management procedure at Sukajadi 02 Public Elementary School. The solution is to record all books and provide category labels on each shelf. The next step is to start implementing a good library management procedure. This study aims to identify the library management procedure in schools, using qualitative research and a case study approach. The results showed that there was no implementation of a good library management procedure at Sukajadi 02 Public Elementary School. The next step is to start implementing a good library management procedure.